2019
DOI: 10.1177/2059513119868345
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression analysis in scars treated with silicone cream: a case series

Abstract: Background: In contrast to fetal scar tissue, adult scar tissue presents with visible scarring. Topical silicone creams have been shown to improve the appearance of scars. This case series compares the genetic expression of post-surgical scar tissues that received topical scar treatment with silicone cream, SKN2017B, or no treatment. SKN2017B is a recently formulated silicone-based scar cream that contains selective synthetic recombinant human growth factors, hyaluronic acid, and vitamin C. We hypothesise that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Mustoe [61] suggested that occlusion and hydration downregulate keratinocyte stimulation and in turn cause a decrease of fibroblast activity. Other studies demonstrated that SGS decreases TGF-β1 and TGF-β2 expression in fibroblasts [62,63], and Kikuchi and co-workers [64] demonstrated that scars treated with silicone gel show favorable gene expression for wound healing. The application of SG promoted the maturation of burn scars in most cases and significantly improved the surface roughness of the scars [65].…”
Section: Silicone Therapymentioning
confidence: 98%
“…Mustoe [61] suggested that occlusion and hydration downregulate keratinocyte stimulation and in turn cause a decrease of fibroblast activity. Other studies demonstrated that SGS decreases TGF-β1 and TGF-β2 expression in fibroblasts [62,63], and Kikuchi and co-workers [64] demonstrated that scars treated with silicone gel show favorable gene expression for wound healing. The application of SG promoted the maturation of burn scars in most cases and significantly improved the surface roughness of the scars [65].…”
Section: Silicone Therapymentioning
confidence: 98%